Meningkatkan Kemampuan Berpikir Kritis Melalui PBL Pendekatan Window Shopping Peserta Didik Kelas VIII di SMP Pangudi Luhur 1 Yogyakarta - Anna Titis Widosari; Mawarni Gea; Agustinus Mulyono (Sekolah Tinggi Pastoral Kateketik (STPKat) Santo Fransiskus Assisi Semarang, 2024)
Various national and international studies show that Indonesia has experienced a long learning crisis, especially during the Covid-19 pandemic. To overcome the crisis and various challenges, systemic changes are needed, one of which is through a curriculum that can affect the speed and teaching methods used by teachers to meet the needs of students. In the independent curriculum, students are expected to be able to carry out their own learning process in decision making. In the world of education, critical thinking skills must be possessed by students in facing challenges in the era of globalization. With critical thinking skills, students can analyze information in depth, make decisions based on logical considerations, and solve problems in an effective way. Meanwhile, many students in class VIII of SMP Pangudi Luhur 1 Yogyakarta are still found to be passive in following the learning process. They more often receive information directly from the teacher without doing much analysis or reflection. The learning approach used in schools also tends to be teacher-centered and is dominated by monotonous lectures and assignments, making students less motivated to think critically and creatively. To overcome these problems, it is very important to have innovation in learning methods that can stimulate students' critical thinking skills. One method that is believed to be effective in improving this ability is Problem-Based Learning (PBL) with a window shopping approach. The objectives of the study include (1) to determine the implementation of Catholic Religious Education learning using the PBL model with a window shopping approach in class VIII of SMP Pangudi Luhur 1 Yogyakarta, (2) to determine to what extent learning with the PBL model with a window shopping approach can improve critical thinking skills of class VIII students at SMP Pangudi Luhur 1 Yogyakarta. The type of research used is qualitative. Data collection techniques in this study used observation, documentation, and field notes. The data collection techniques used consisted of data reduction from the field which was recorded in detail and carefully through observation, data presentation in the form of tables, graphs, and diagrams and drawing conclusions from the research results that refer to the formulation of the problem. The use of the Problem Based Learning model with a window shopping approach is effective in helping to improve critical thinking skills of students on the material of the Calling and Mission of Jesus' Disciples in class VIII of SMP Pangudi Luhur 1 Yogyakarta.